Cortometraje 3D sobre la leyenda quiteña La Casa 1028 - Dávila Samaniego, Kleber Jeferson (2016)
This project aims to create a 3D animated short film based on the legend of Quito La casa 1028 which seeks to promote the rapprochement of the youth audience. The development of the audiovisual product meets the current demands of young people of Quito by modern graphic styles, proposing innovative alternatives in creating arguments subject to the expressions and contemporary realities. The results of the procedure show the lacking relationship between Quito and traditional methods of patrimonial expression, culture is cracking with the advent of new digital media, however, these can be assigned to improve the local culture with positive returns as shown below.